Best practice for clinical hydration measurement - Minton, D. M.; Eberman, L. E. (Athletic Therapy Today, 2009)
The article looks at the best practice for the clinical measurement of hydration as it relates to sports medicine. The risks of dehydration in athletes are discussed. The use of a refractometer to measure urine specific gravity is recommended by the author as a reliable clinical measuring tool. Changes in body mass or urine color are common indicators of hydration status.